In situ observations of silica nanoparticle growth in geothermal brine at the Sumikawa geothermal station, Japan, by dynamic light scattering. (January 2019) - Tamura, Ryo; Inoue, Hitoshi; Hanajima, Eri; Ikeda, Risa; Osaka, Yuji; Yanaze, Takumi; Kusakabe, Minoru; Yonezu, Kotaro; Yokoyama, Takushi; Tsukamoto, Katsuo; Marumo, Katsumi; Ueda, Akira
Highlights: Silica nanoparticle growth in geothermal brine is examined during the polymerization of silicic acid by observation with dynamic light scattering at the Sumikawa geothermal station. Three types of geothermal brines, raw (pH 6.6), pH adjusted (pH 8), and diluted brines were examined. The monosilicic acid concentration rapidly decreased over time in the raw brine but was almost constant in the samples with lower silicic acid concentrations. The polysilicic acid particle diameters in the raw brine increased from 1 to 6 nm within 5 min and then was almost constant at 7 nm for the subsequent 30 min. Abstract: Silica nanoparticle growth in geothermal brine was examined during the polymerization of silicic acid by observation with dynamic light scattering (DLS) at the Sumikawa geothermal station, examining raw (pH 6.6), pH adjusted (pH 8), and diluted brines (100 to 60%). The monosilicic acid concentration rapidly decreased over time in the raw brine but was almost constant in the samples with lower silicic acid concentrations. The average polysilicic acid particle diameter in the raw brine rapidly increased, from 1 to 6 nm, within 5 min (stage I) and then was almost constant at 7 nm for the subsequent 30 min (stage II).